2020
DOI: 10.4102/sajce.v10i1.802
|View full text |Cite
|
Sign up to set email alerts
|

Proposing and modifying guided play on shapes in mathematics teaching and learning for Zambian preschool children

Abstract: An increasing number of studies have discussed the development of early childhood education (ECE) programmes in different countries (Müller & Wittmann 2004a, 2004b South African Numeracy Chair Project 2016), the improvement of teachers' pedagogical content knowledge (Lee 2017;McCray & Chen 2008) and their professional development (Warren & Quine 2013). Recent studies have revealed that children can engage in many mathematical practices, such as Background: Early childhood education (ECE) has recently been int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
(44 reference statements)
1
11
0
1
Order By: Relevance
“…Through play in early Mathematic, Nordin and Romarzila (2022) lists several sections in prenumber concepts. The finding match with the sections in pre-number concepts which are identify skills (Nakawa, 2020), matching skills (Ramani & Scalise, 2020), comparing skills (Nakawa, 2020), organize skills (Vanbecelaere et al, 2020), reasoning skills (Outwaite et al, 2019, and skills of understanding the concept of numbers (Lange et al, 2021;Ramani et al, 2020). By the way, classify skills not found in the present studies.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Through play in early Mathematic, Nordin and Romarzila (2022) lists several sections in prenumber concepts. The finding match with the sections in pre-number concepts which are identify skills (Nakawa, 2020), matching skills (Ramani & Scalise, 2020), comparing skills (Nakawa, 2020), organize skills (Vanbecelaere et al, 2020), reasoning skills (Outwaite et al, 2019, and skills of understanding the concept of numbers (Lange et al, 2021;Ramani et al, 2020). By the way, classify skills not found in the present studies.…”
Section: Discussionsupporting
confidence: 85%
“…We found that very few study examined on dimension of learning through play. Nakawa (2020) examined on guided play. This finding reflects there is very few studies towards dimension of learning through play.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informal mathematical activities should be undertaken for a solid foundation of mathematical concepts and skills for further education. In pre-mathematics ata mathematics for early childhood includes algebra, numbers, geometry, measurement, and commercial arithmetic (Nakawa, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research related to playing mathematics and semiotics has been carried out by many previous researchers, including (Nakawa, 2020) the results of their research show that guided play is effective during the planned activities according to the child's socio-cultural background and readiness. From a curriculum development point of view, first, matching activities can be carried out when the child is accustomed to flexible form manipulation in the classroom.…”
Section: Introductionmentioning
confidence: 99%